2022
DOI: 10.1051/epjconf/202225910004
|View full text |Cite
|
Sign up to set email alerts
|

Spectral reconstruction details of a gradient-flowed color-electric correlator

Abstract: In a recently published work we provide a proof-of-concept of a novel method to extract the heavy quark momentum diffusion coefficient from color-electric correlators on the lattice using gradient flow. The transport coefficient can be found in the infrared limit of the corresponding spectral function which is reconstructed through perturbative model fits of the correlator data. In this proceedings report we want to give more detailed insights into the systematic uncertainties of this procedure and compare our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Let us denote this term by κ E . Many lattice studies of κ E have been reported in quenched QCD [6][7][8][9][10][11][12], and even though further improvements are desirable, related for instance to non-perturbative renormalization, unquenching, and analytic continuation, the patterns that have emerged so far point towards a consistent picture.…”
Section: Introductionmentioning
confidence: 99%
“…Let us denote this term by κ E . Many lattice studies of κ E have been reported in quenched QCD [6][7][8][9][10][11][12], and even though further improvements are desirable, related for instance to non-perturbative renormalization, unquenching, and analytic continuation, the patterns that have emerged so far point towards a consistent picture.…”
Section: Introductionmentioning
confidence: 99%
“…Beside this phenomenological estimate, in this work we also employ lattice-QCD (lQCD) results for D s taken from Ref. [16].…”
Section: The Fokker-planck Equation and Heavy-quark Transport Coeffic...mentioning
confidence: 99%
“…Here and in the next plots the range spanned by τ n is highlighted by the colored bands. Different colored bands correspond to different D s estimates coming from lattice-QCD simulations [16] and from fits to ALICE experimental data [15]. The heavy-quark relaxation time increases linearly with the M/T ratio when the latter is large enough.…”
Section: B Heavy-quark Relaxation Timementioning
confidence: 99%
See 2 more Smart Citations